أنماط الحجة في خطاب المتحدثين في بطولة المناظرة باحتفال مؤسسات التعليم العالي بجامعة العلوم الإسلامية ماليزيا سنة 2018 - Elhaq, Seif Robert; Mahliatussikah, Hanik; Kholisin (Shaut al Arabiyyah, 2023)
This article aims to describe the pattern of argumentation in the speakers’ rhetoric at the Arabic debate championship in the Ihtifal Institusi Pengajian Tinggi (IPT) at Universiti Sains Islam Malaysia 2018. The speakers’ rhetoric is studied based on the so-called Toulmin’s Argumentation Pattern (TAP) which consists of six elements of argument, namely C (claim), statement, G (ground) reason or evidence, W (warrant) guarantee, B (backing) support, M (modal qualifier) ​​certainty of statement, and R (rebuttal) disclaimer. In addition, the research method used is a qualitative description with content analysis techniques. The data collection technique in this study is a documentation technique in the form of recorded data on Arabic debates on YouTube with a total of 3 videos and each video has a duration of 8 minutes. The research findings reveal that there are 14 patterns of argumentation in the rhetoric of the three contra team speakers. The rhetoric of the first contra speaker includes various ideas forming the first pattern C (Claim) and G (Ground) 2 times, and the fourth pattern C (Claim), G (Ground), W (Warrant), M (Modal qualifier) ​​and R (Rebuttal) mentioned once. Moreover, the rhetoric of the second contra speaker includes various ideas forming the first pattern C (Claim) and G (Ground) mentioned once, the second pattern C (Claim), G (Ground), and R (Rebuttal) mentioned once, and C (Claim), M (Modal qualifier) ​​and R (Rebuttal) mentioned once, and the third pattern is C (Claim), G (Ground), M (Modal qualifier) ​​and R (Rebuttal) mentioned once, and pattern C (Claim), G (Ground), W (Warrant), M (Modal qualifier). Furthermore, the rhetoric of the third contra speaker includes various ideas forming the first pattern C (Claim) and R (Rebuttal) 3 times, the second pattern C (Claim), G (Ground) and R (Rebuttal) twice, and the third pattern C (Claim), G (Ground), M (Modal qualifier) ​​and R (Rebuttal) mentioned once.